2003
DOI: 10.2134/jeq2003.3350
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Phosphorus Sorption Capacity in a Semiarid Altered Wetland

Abstract: The observed increase in phosphorus (P) loading into the Jordan River could increase eutrophication processes in Lake Kinneret, the only freshwater lake in Israel, which provides 25% of the country's drinking water. The P may originate from the peat soils of the highly altered Hula Valley's semiarid wetland ecosystem through which the Jordan River runs. The objectives of this research were to ascertain the sorption capacity of these soils and to identify areas with high potential for P release from soils to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 17 publications
(22 reference statements)
2
26
1
Order By: Relevance
“…Commonly, univariate geospatial methods are used to model the distribution and variation of soil properties in wetland ecosystems. For example, Newman et al (1997) predicted soil NH 4 -nitrogen, soluble reactive phosphorus, total phosphorus (TP), and total nitrogen (TN) in a subtropical wetland in Florida; DeBusk et al (2001) predicted TP in Water Conservation Area-2A (WCA-2A), Everglades; Litaor et al (2003) predicted soil phosphorus, iron, aluminum, calcium and degree of phosphorus saturation in a semiarid wetland; and Bruland and Richardson (2005) predicted soil organic matter and sand content in four paired created/restored and natural wetland sites in the Coastal Plain of North Carolina. Since anthropogenically-induced phosphorus inputs stimulate microbial, periphyton and macrophyte growth in naturally oligotrophic wetlands, it is critical to describe spatial patterns of soil phosphorus to better understand processes of phosphorus retention, availability and release.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, univariate geospatial methods are used to model the distribution and variation of soil properties in wetland ecosystems. For example, Newman et al (1997) predicted soil NH 4 -nitrogen, soluble reactive phosphorus, total phosphorus (TP), and total nitrogen (TN) in a subtropical wetland in Florida; DeBusk et al (2001) predicted TP in Water Conservation Area-2A (WCA-2A), Everglades; Litaor et al (2003) predicted soil phosphorus, iron, aluminum, calcium and degree of phosphorus saturation in a semiarid wetland; and Bruland and Richardson (2005) predicted soil organic matter and sand content in four paired created/restored and natural wetland sites in the Coastal Plain of North Carolina. Since anthropogenically-induced phosphorus inputs stimulate microbial, periphyton and macrophyte growth in naturally oligotrophic wetlands, it is critical to describe spatial patterns of soil phosphorus to better understand processes of phosphorus retention, availability and release.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated a minor risk of P leaching losses if the threshold of 25% for mineral soils was assumed (Breeuwsma and Silva 1992;Schoumans and Groenendijk 2000). An extensive study of DPS distribution in the Hula Valley demonstrated a strong correlation between the sorption maxima (S max ) derived from evaluations of adsorption isotherms by the Langmuir equation and the DPS, indicating that DPS could be applied both to mineral and organic soils at the catchment scale (Litaor et al 2003). In that study, the DPS values were much lower in Histosols (6.5±5) than in redoximorphic Gley soils from marl (28±18) and Vertisols (78±28).…”
Section: Characterisation Of Soil P Status P Adsorption and P Mobilimentioning
confidence: 99%
“…In that study, the DPS values were much lower in Histosols (6.5±5) than in redoximorphic Gley soils from marl (28±18) and Vertisols (78±28). Spatial analysis with a sequential Gaussian simulation technique further indicated that the Histosols had a much lower risk (<10%) of exceeding the commonly used threshold of 25% DPS than redoximorphic Gley soils from marl and Vertisols (>60% probability) (Litaor et al 2003). However, it is doubtful if the thresholds developed for assessments of P leaching risks in sandy acid soils could be applied for the problem of fen peat rewetting.…”
Section: Characterisation Of Soil P Status P Adsorption and P Mobilimentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there was an increase in suspended material and nitrate loadings into the Sea of Galilee from the Hula Basin via the Jordan River (Litaor et al 2003), with peat being listed as a major source of pollution in the first Sea of Galilee master plan (Salik 1975). Due to water shortages, the water supplied to the Hula Nature Reserve was wastewater from fishponds (Paz 1975).…”
Section: Water Purificationmentioning
confidence: 99%